An Enzyme Linked Immunosorbent Assay for Determination of Tissue Plasminogen Activator Applied to Patients with Thromboembolic Disease - Bergsdorf, Nils; Nilsson, Torbjörn; Wallén, Per (Thrombosis and Haemostasis, 1983)
Utilizing the immunoglobulin fraction from a goat antiserum against human uterine tissue plasminogen activator, an enzyme- linked immunoassay for tissue-type plasminogen activator in human plasma has been developed. With the new method, the concentration of t-PA in normal human acidified plasma is found to be 4.0 ± 1.8 (SD) ng/ml. It increases to 12 ng/ml after a tomiquet test, and to 14 ng/ml after strenous physical exercise. In a group of patients with idiopathic thromboembolic disease, the resting t-PA concentration was 5 ng/ml and the post-occlusion value 16 ng/ml. Furthermore, the patients also exhibited a normal post-occlusion rise in the concentration of plasmin-α2-antiplasmin complex. However, in 37% of the post-occlusion patient plasmas, virtually no increase in t-PA could be detected by a specific activity assay. The results indicate that the reason for a defective post-occlusion fibrinolytic activity in a majority of cases may be the presence of increased concentrations of a fast-acting specific t-PA inhibitor.
Keywords: ELISA; Tissue-type plasminogen activator; Thromboembolic disease